Dielectric strength of surfaces of dielectrics in microwave fields of nanosecond duration; Radioelectronics and Communication Systems; Vol. 30, № 8 - Novikov S. A. Sergey Avtonomovich; Razin S. V.; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich (1987, 1987)
В фонде НТБ ТПУ отсутствует